The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2169/internalmedicine.52.9505
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Remission in Patients with Acute Myeloid Leukemia with t(8;21) or Cutaneous Myeloid Sarcoma: Two Case Reports and a Review of the Literature

Abstract: Spontaneous remission (SR) in patients with acute myeloid leukemia (AML) is rare. We herein present two such cases. The first case was of AML-M2 accompanied by a bone marrow cytogenetic analysis revealing 46, XY, t(8;21)(q22,q22). The second case was of isolated cutaneous myeloid sarcoma (MS) that progressed to AML within seven months. Both of the patients had symptoms of infection and anemia and were therefore treated with antibiotics and transfusions. The SR lasted for two months and one month, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
8
3
Order By: Relevance
“…8,11,13 A statistically significant correlation between fusion transcripts involving the core-binding factor (CBF) complex (RUNX1-RUNX1T1 and CBFB-MYH11) and de novo MS has been reported in other studies. 12,[17][18][19] In our patient cohort, we also found an association between these fusion genes and de novo MS. According to the literature, orbital presentations of MS are often associated with t(8;21) (q22;q22) or KMT2A rearrangements, while the presence of an inv (16) in MS cases seems to be associated with intestinal involvement.…”
Section: Discussionsupporting
confidence: 74%
“…8,11,13 A statistically significant correlation between fusion transcripts involving the core-binding factor (CBF) complex (RUNX1-RUNX1T1 and CBFB-MYH11) and de novo MS has been reported in other studies. 12,[17][18][19] In our patient cohort, we also found an association between these fusion genes and de novo MS. According to the literature, orbital presentations of MS are often associated with t(8;21) (q22;q22) or KMT2A rearrangements, while the presence of an inv (16) in MS cases seems to be associated with intestinal involvement.…”
Section: Discussionsupporting
confidence: 74%
“…Potential other contributing factors including granulocyte-colony stimulating factor (GCSF) administration and hormonal changes (both of which could also impact on innate immune function) have been reported [43]. There is also data suggesting that certain biological subsets of AML may be more likely to undergo SR, specifically FAB subtypes M4/M5 which constitute about half of all reported cases of SR in AML, and certain cytogenetics [3, 4]. Of note, patients with NPM1 mutant AML similar to our patient may also be predisposed towards SR [3, 44].…”
Section: Discussionmentioning
confidence: 99%
“…There is also data suggesting that certain biological subsets of AML may be more likely to undergo SR, specifically FAB subtypes M4/M5 which constitute about half of all reported cases of SR in AML, and certain cytogenetics [3, 4]. Of note, patients with NPM1 mutant AML similar to our patient may also be predisposed towards SR [3, 44]. The presence of NPM1 mutation, found in approximately 35% of AML cases, is known to confer favorable prognosis [45, 46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For certain patients, where myeloid sarcomas are accompanied by other hematological diseases, systemic chemotherapy or combined treatment with surgical removal, local radiotherapy and systemic chemotherapy may be performed, depending on the particular situation of each individual patient (8). Although previous studies have reported the spontaneous remission of myeloid sarcomas (25), the majority of these were accompanied with other hematological diseases (18). Therefore, treatment is required to improve the survival rate of patients with myeloid sarcoma.…”
Section: Discussionmentioning
confidence: 99%